Effect of Plate–Bone Distance and Screw Number on 2.0-mm Locking Construct Torsional Stiffness and Plate Strain in a Diaphyseal Fracture Gap Model - Evans, Alecia; Glyde, Mark; Hosgood, Giselle; Day, Rob (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
To determine the effect of plate–bone distance and screw number on 2.0-mm locking compression plate (LCP) torsional stiffness and plate strain for a fixed working length in a diaphyseal fracture gap model.In vitro biomechanical study.The LCP was tested with nine different combinations of plate–bone distance (PBD) (1, 1.5, and 3 mm) and screw number (SN) (two, three, or four screws per fragment) across the same working length. Six replicates per group were tested. Constructs were subjected to quasi-static, non-destructive torsion producing overall construct stiffness data (Nm/degree). Plate surface strain data were recorded from three-dimensional digital image correlation during testing for all constructs.A greater PBD and a low SN resulted in lower construct stiffness (p = 0.015, and P > 0.0001, respectively) in torsion. Across all PBD, there was significantly less stiffness for constructs with two screws per fragment, compared with three screws or four screws. No significant difference was detected in plate strain for any combination of PBD and SN.In this model, incrementally increasing the PBD and decreasing the SN resulted in less construct stiffness in torsion, with marked reduction in torsional stiffness in constructs with two screws per fragment compared with three or four screws per fragment.
Keywords: biomechanics; fracture repair; locking plates; screw number; plate–bone distance